Cobalt-catalyzed tandem one-pot synthesis of polysubstituted imidazo[1, 5-a]pyridines and imidazo[1, 5-a]isoquinolines. Issue 20 (12th May 2022) - Meena, Neha; Dhiman, Shiv; Rangan, Krishnan; Kumar, Anil
Abstract : An efficient cobalt-catalyzed tandem one-pot method has been developed for the synthesis of polysubstituted imidazo[1, 5- a ]-N-heteroaromatics. Abstract : An efficient cobalt-catalyzed tandem one-pot method has been developed for the synthesis of polysubstituted imidazo[1, 5- a ]-N-heteroaromatics. The method involves Knoevenagel condensation followed by cobalt-catalyzed direct alkenylation to give the desired polysubstituted imidazo[1, 5- a ]pyridines and imidazo[1, 5- a ]isoquinolines in a one-pot manner. This method exhibits a broad substrate scope, provides moderate to good (39–74%) yields and is amenable to scale-up to the gram scale.